Perceived obstacles for business development: Construct development and the impact of farmers' personal values and personality profile in the Swedish agricultural context. (January 2021) - Hansson, Helena; Sok, Jaap
Abstract: The objective of this study was twofold: first, to assess the empirical content and structure of farmers' perceptions of obstacles for business development, and second, to explore how individual differences between farmers relate to these perceptions. The study is based on survey data collected from Swedish agriculture in 2018. We estimated a latent variable representing farmers' perception of obstacles for business development using a MIMIC model approach and included measures of personal values and personality traits to the model to take into account individual differences. The findings suggest that the surveyed farmers' perceptions of obstacles for the development of their businesses centre around the following areas: access to financial resources; farm layout (in terms of physical layout of the farmyard and fields) and geographical location; consumer demand; available resources and options for farm succession. Only individual differences in terms of personality traits that relate to entrepreneurship (extraversion and openness), could be related to the perceived obstacles. The findings are useful for prioritising agricultural policy and for the design of extension and advisory services aimed at assisting farmers to develop their business – particularly in Sweden but also in regions similar to Sweden. Furthermore, the approach developed here is informative for other policy makers and advisory services interested in prioritising efforts to better support farmers' business development. Highlights: A latent variable perceived obstacles for business development (POBD) is developed. The empirical content and structure of farmers' POBD is assessed. Farmers' POBD centres around the areas: resources, location, demand and succession. Differences in farmers' POBD relate to personality traits, not to personal values. Findings are useable for prioritising policy measures and designing advisory services.